PENILAIAN POSTUR KERJA PEKERJADENGAN MENGGUNAKAN METODEOVAKO WORKING POSTURE ANALYSIS SYSTEM(OWAS) DI UD. KEPUH NUTRINDO - , RR. MELLA MIANDI, Dr. Ir. Makhmudun Ainuri, M. Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ud. Kepuh nutrindo an industry engaged in the processing melinjo. Melinjo manufacture workstations consists of three elements work, ie roasting, peeling shell, and flating. Each element of work in progress for a long time and done repeatedly with the same working position. Work that is done repeatedly and for long periods of time can cause workers to experience pain in the muscles or back. Suitable method for the assessment of the work that is less ergonomic posture at work station in the manufacture melinjo UD. Kepuh Nutrindo is a method Ovako Work Posture Analysis System or OWAS. OWAS methods used to analyze and observe the movement of the back, arms, legs, and lifted weights to obtain the category workload performed by the worker. Results of the analysis owas a workload category will be used for the repair job position in the future. Work area consists of the minimum and maximum work area, work area inu distinguished from the position of the reach of the hands of workers.